A Collaborative Service Discovery and Service Sharing Framework for Mobile Ad Hoc Networks - Safa, Haidar (2007)
Service sharing and discovery play a relevant role in mobile ad hoc environments. Upon joining a self-organizing network, mobile nodes should be able to explore the environment to learn about, locate, and share the available services. In this paper, we propose a distributed and scalable service discovery and sharing framework for ad hoc networks. The proposed framework defines three types of nodes: service directories, service providers and requesting nodes. Service directory nodes act as mediators for lookup requests from requesting nodes. Joining service provider nodes register their services with the nearest service directory. A requesting node discovers the available services by submitting requests to its nearest service directory which determines the node providing the requesting service. The performance of the proposed model is evaluated and compared to the broadcast-based model that has been extensively studied in the literature.